Exploring the Figurative Languages of Because I Could Not Stop for Death by Emily Dickinson.pdf - Sharikha, Zhillan; Laksminy, Luh Putu; Utami, Gek Wulan Novi (Jurnal Ilmiah Wahana Pendidikan, 2026)
This article aims to unravel the layers of meaning embedded in the poem by analyzing and identifying intrinsic elements, such as imagery and figurative language, in Emily Dickinson's “I Could Not Stop for Death.” Imagery is used to make readers feel things through their five senses. On the other hand, figurative language is a form of speech craftily varied from ordinary usage. The method used in this article was a descriptive qualitative approach. Reading the poem in order to comprehend its overall meaning and discover the meaning that was primarily the essence related to the topic was how the data was collected. In this article, there are four figurative languages found, which are Personification, Metaphor, Symbolism, and Hyperboles